2022
DOI: 10.1002/ece3.8883
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in song plasticity in response to social stimuli and singing position

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Some studies have suggested that differences in habitat type can lead to variation in birds’ singing height and post sites [ 40 , 41 , 42 ]. According to our results, oriental magpie-robins in low-rise residential areas sang at a higher position and made more use of artificial buildings than those in urban parks.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that differences in habitat type can lead to variation in birds’ singing height and post sites [ 40 , 41 , 42 ]. According to our results, oriental magpie-robins in low-rise residential areas sang at a higher position and made more use of artificial buildings than those in urban parks.…”
Section: Discussionmentioning
confidence: 99%
“…In conflict situations, for example, acoustic signals may be favored rather than physical combat, as the latter poses risks of injury, higher energy expenditure, or death [4]. Acoustic signals can exhibit plasticity and vary structurally (e.g., in frequency or duration) depending on the costs of those signals [5], signaler motivation [6], environment [7], urbanization [8], anthropogenic noise [9], and the social pressures exerted on these signals [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, courtship song is driven by reproductive motivation, while spontaneous song can occur even in social isolation (Sossinka and Böhner 1980). These two types of song rarely differ in their structure and syntax, but rather in their spectral characteristics such as song stereotypy (Ota and Gahr 2022), length and frequency (Gémard et al 2021;Jablonszky et al 2022), tempo and amplitude (Riebel 2009). The reproductive status of a male can also be communicated by its song parameters.…”
mentioning
confidence: 99%